Development of an Interface for the Control of Robotic Exoskeletons Based on Stroke Rehabilitation Techniques - Barría, P.; Aguilar Cardenas, Rolando Nemecio; Unquen, D.; Moris, A.; Andrade, A.; Biskupovic, A.; Azorín, J.M. (My University, 2022)
This work presents the development and implementation of an interface to control a robotic exoskeleton for gait rehabilitation in patients with stroke through exercises based on conventional neuro-rehabilitation therapies. Movement patterns of each exercise were acquired using an optoelectronic ten-camera system in a group of subjects without pathology. An interface for robotic control was developed in the LABVIEW environment that allows kinematics of each exercise to be reproduced in a robotic exoskeleton. The interface allows us to control: the assistance percentage, movement patterns, movement speed, number of repetitions, and resting time. The software presents plot panels for each joint that shows programmed kinematic and executed curves in real-time as a feedback tool for therapist. Finally, the kinematic data is stored in a directory with the patient's name and session date for post-analysis.
Keywords: Interface (matter); Stroke